The Association between Coffee Consumption and Local Anaesthesia Failure - Ayah Al Hanish; Dalal Almghairbi; Mohamed Almgerbe; Amina Shimu; Hala Ali; Marwa Aqeel (AlQalam Journal of Medical and Applied Sciences, 2025)
Some patients report inadequate numbness following local anaesthesia, requiring higher-than-normal doses. Caffeine consumption has been suggested to reduce anaesthetic effectiveness. This study aimed to evaluate the effect of caffeine intake on the effectiveness of local anaesthesia during dental treatment. A cross-sectional, self-reported survey was conducted in Zawia City, Libya, between April and June 2025 among patients attending dental clinics. The questionnaire assessed demographic characteristics, caffeine consumption, medical history, and perceived anaesthetic effectiveness. Validity and reliability were evaluated by specialists in anaesthesia, dentistry, epidemiology, and biostatistics. Of 150 distributed questionnaires, 94 were completed (62.7%). More than half of the participants required two or more local anaesthetic injections to achieve numbness. Higher coffee consumption and intake of other caffeinated beverages were significantly associated with reduced perception of anaesthetic numbness and increased injection requirements (p < 0.005). However, only 4.1% of participants self-reported that caffeine affected anaesthetic success. In conclusion, while most patients did not perceive caffeine as affecting local anaesthesia, higher caffeine intake was statistically associated with reduced anaesthetic effectiveness. These findings may relate to caffeine’s effects on alertness, stress, and anxiety. The single-centre design and limited sample size restrict generalizability; therefore, larger multicentre studies are recommended.